Praise Private Rational Strategy Daily in Building Company Image - Zalikha, Azra; Harahap, Nursapiah; Abidin, Syahrul (Pena Cendekia Insani, 2023)
Harian Waspada is a print media company that was founded in 1947. During that time, this company managed to attract the attention of the people of Medan, especially the city of Medan, who were looking for information through print media. The public relations strategy in building the company's image for the public is the main factor that makes Harian Waspada famous and in great demand. Therefore, the author wants to find out how Waspada's public relations strategy builds the company's image as new knowledge for personal writers and other audiences.